Enhancing Knowledge and Awareness of Routine Hypertension Control and Medication in Panjang Jiwo, Surabaya - Kellyn Trycia Zenjaya; Ronald Pratama Adiwinoto; Callista Vivien Earlyanti; Bima Abdul Azis; Yahdiyan Fathir Fadhilah; Fairuziah Dinda Umardy; Amalia Dewindra Candra Puspita; Sekar Kurnia Cahya; Dinnara Nelya Rindayu; Vania Roanna Gabrielle (Promotif : Jurnal Kesehatan Masyarakat, 2025)
Background: The Tenggilis Public Health Center (Puskesmas Tenggilis) is devoted to implementing Community Health Efforts (UKM) to ensure the provision of high-quality healthcare services, focusing on the measurement, monitoring, and supervision of local health problems. A Self-Assessment Survey (Survey Mawas Diri” (SMD) in Indonesian language) was conducted in Panjang Jiwo Village, Surabaya, revealing hyperten”sion as a primary health issue. Characterized by a systolic blood pressure ?140 mmHg and a diastolic pressure ?90 mmHg, hypertension remains widespread, with many residents unaware of the necessity for lifelong medication adherence and routine blood pressure monitoring. Methods: To address this health challenge, a thorough analysis was conducted, examining the root causes through the "man, method, machine, and material" framework. This approach informed the development of a targeted intervention strategy. Results:The intervention involved designing and distributing a Hypertension Calendar, providing an accessible means for residents to record their blood pressure readings and track medication adherence throughout the year. The calendar serves as a useful tool during healthcare visits, fostering enhanced dialogue between patients and healthcare providers regarding hypertension management. Conclusions: The introduction of the Hypertension Calendar aims to empower individuals with essential knowledge and tools for effective hypertension management, ultimately contributing to improved health outcomes in the Panjang Jiwo community. Key words: Hypertension; Community Empowerment; Public Health; Health Promotion; Health Education